Arabidopsis SUC1 loads the phloem in suc2 mutants when expressed from the SUC2 promoter. - Wippel, Kathrin; Sauer, Norbert (Journal of Experimental Botany, 2012)
Active loading of sucrose into phloem companion cells (CCs) is an essential process in apoplastic loaders, such as Arabidopsis or tobacco (Nicotiana sp.), and is even used by symplastic loaders such as melon (Cucumis melo) under certain stress conditions. Reduction of the amount or complete removal of the transporters catalysing this transport step results in severe developmental defects. Here we present analyses of two Arabidopsis lines, suc2-4 and suc2-5, that carry a null allele of the SUC2 gene which encodes the Arabidopsis phloem loader. These lines were complemented with constructs expressing either the Arabidopsis SUC1 or the Ustilago maydis srt1 cDNA from the SUC2 promoter. Both SUC1 and Srt1 are energy-dependent sucrose/H(+) symporters and differ in specific kinetic properties from the SUC2 protein. Transgene expression was confirmed by RT-PCRs, the subcellular localization of Srt1 in planta with an Srt1-RFP fusion, and the correct CC-specific localization of the recombinant proteins by immunolocalization with anti-Srt1 and anti-SUC1 antisera. The transport capacity of Srt1 was studied in Srt1-GFP expressing Arabidopsis protoplasts. Although both proteins were found exclusively in CCs, only SUC1 complemented the developmental defects of suc2-4 and suc2-5 mutants. As SUC1 and Srt1 are well characterized, this result provides an insight into the properties that are essential for sucrose transporters to load the phloem successfully.